ECMO support in SARS-CoV2 multisystem inflammatory syndrome in children in a child. (July 2021) - Kaushik, Shubhi; Ahluwalia, Neha; Gangadharan, Sandeep; Esperenza, Maria; Murthy, Raghav; Ofori-Amanfo, George; Aydin, Scott I
In this report, we describe the case of a 5-year-old male with SARS-CoV-2 associated MIS-C with progressive respiratory failure and vasoplegic shock requiring extracorporeal support. At presentation, reverse transcription-polymerase chain reaction (RT-PCR) testing for SARS-CoV-2 was negative, however, SARS-CoV2 antibody testing was positive. Multiple inflammatory markers and cardiac biomarkers were elevated. Echocardiogram demonstrated mildly depressed left ventricular function and no coronary anomalies noted. The patient required mechanical ventilation, vasopressors, and eventually extracorporeal membrane oxygenation (ECMO) for profound circulatory shock and progressive respiratory failure. During his clinical course, recovery of cardiac function was demonstrated however, a middle cerebral artery infarct and left frontal subarachnoid hemorrhage was suffered which ultimately the patient succumbed to. To the best of our knowledge, this is the youngest previously healthy child who had multi-system hyperinflammatory syndrome requiring ECMO support and the first case of SARS-CoV-2 related pediatric stroke. Clinical Trial Registration: None